Rethinking language teacher training: steps for making talk-in-interaction research accessible to practitioners. Issue 1 (2nd January 2019) - Huth, Thorsten; Betz, Emma; Taleghani-Nikazm, Carmen
ABSTRACT: The goal of this paper is to enhance the quality of language teaching and improve language teacher training by making spoken interaction research accessible to practitioners. Research on teacher cognition has shown that basic beliefs and assumptions about language affect language teacher training programs and language teachers' priorities in the classroom. Such beliefs tend to reflect teachers' own socialization and orient to current administrative guidelines in L2 teaching, often resulting in a focus on language production of individual speakers. In contrast, a social-interactionist perspective emphasizes the co-constructed nature of language and interaction. Unpacking teachers' beliefs and their consequences for what is taught is necessary for implementing interactional competence-based instruction. This paper suggests concrete steps to facilitate teacher training, preparing language teachers for Conversation Analysis-based Interactional Competence instruction. Such training includes, (1) sustained critical reflection of teachers' conceptions of what language is, (2) basic training of pre- and in-service teachers in micro-analytic procedures that enable the analysis of actual talk-in-interaction, and (3) models for translating and transferring research on spoken communication and interaction into pedagogical practice. These teacher training elements: advance an empirically informed, state-of-the art view on interactional competence (IC); provide teachers with the necessary tools for meaningful, reflexive work with IC materials; and can supplement current methodology textbooks.